Mediating Factors in Nursing Competency: A Structural Model Analysis for Nurses’ Communication, Self-Leadership, Self-Efficacy, and Nursing Performance - Kim, Ae Young (Int J Environ Res Public Health, 2020)
This study examined the structural relationship among clinical nurses’ communication ability, self-leadership, self-efficacy, and nursing performance. A structural model analysis was applied to identify factors influencing nursing performance and analyze the effects of self-leadership and self-efficacy as mediators. A survey was conducted among clinical nurses working in general hospitals in Seoul, Gyeonggi, and Gangwon Province of the Republic of Korea. In the final analysis, data from 168 questionnaires were used. SPSS 24.0 and Amos 23.0 programs were used for frequency analysis, exploratory factor analysis, reliability analysis, correlation analysis, confirmatory factor analysis, structural equation model analysis, and mediating effect analysis through bootstrapping. The significance level was set at 5% for all analyses. First, the model’s fitness figures met the criteria for the appropriate judgment presented in previous studies, so the model between nurses’ communication ability, self-leadership, self-efficacy, and nursing performance was suitable for predicting a causal relationship. Second, the relationship between nurses’ communication ability and self-leadership had a statistically significant effect. Also, the relationship between communication ability and self-efficacy had a statistically significant effect. Third, nurses’ communication ability affected nursing performance through self-efficacy.